2020
DOI: 10.1037/pas0000819
|View full text |Cite
|
Sign up to set email alerts
|

Self-Injurious Thoughts and Behaviors Interview—Revised: Development, reliability, and validity.

Abstract: The Self-Injurious Thoughts and Behaviors Interview (SITBI) is a widely used measure of the presence, frequency, and characteristics of suicide and self-harming thoughts and behaviors. In response to advances in the conceptualization of these outcomes, and the potential for online data collection, we created a revised version of the SITBI (SITBI-R) and tested its psychometric properties via in-person interview and online self-report formats. Across two studies, the SITBI-R demonstrated strong psychometric prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 49 publications
2
97
0
Order By: Relevance
“…Nock et al (2007) reported the Self-Injurious Thoughts and Behaviors Interview has strong interrater reliability overall (κ = .99) and near perfect agreement on indices of NSSI (κ = .91 to κ = 1.0). These results are consistent with reports from Fox et al (2020), who found near perfect agreement on indices of NSSI (κ = .84).…”
Section: Nssi Historysupporting
confidence: 92%
See 1 more Smart Citation
“…Nock et al (2007) reported the Self-Injurious Thoughts and Behaviors Interview has strong interrater reliability overall (κ = .99) and near perfect agreement on indices of NSSI (κ = .91 to κ = 1.0). These results are consistent with reports from Fox et al (2020), who found near perfect agreement on indices of NSSI (κ = .84).…”
Section: Nssi Historysupporting
confidence: 92%
“…), as well data regarding thoughts of engaging in NSSI. The Self-Injurious Thoughts and Behaviors Interview has been administered to both adult and adolescent populations (Fox et al, 2020;Nock et al, 2007). Nock et al (2007) reported the Self-Injurious Thoughts and Behaviors Interview has strong interrater reliability overall (κ = .99) and near perfect agreement on indices of NSSI (κ = .91 to κ = 1.0).…”
Section: Nssi Historymentioning
confidence: 99%
“…Suicidal ideation was assessed with the self-report version of the Self-Injurious Thoughts and Behaviors Interview-Revised. 20 This tool assesses for suicidal ideation by asking participants to identify which of 8 different suicide-related thoughts they have experienced in their lifetime, the past year, and the past month. For this study, an individual was considered to have suicidal ideation for a given timeframe if they endorsed any of the 8 suiciderelated thoughts during that timeframe.…”
Section: Q6mentioning
confidence: 99%
“…and one question assessing lifetime history of suicide attempts (i.e., "Have you ever tried to kill yourself?"). This has been validated in adolescents, and modules for suicidal ideation and attempt reveal perfect interrater reliability for lifetime presence of suicidal ideation and attempt, as well as excellent convergent validity with the SIQ (Fox et al, 2020;Gratch et al, in press).…”
Section: Self-injurious Thoughts and Behaviors Interview-revisedmentioning
confidence: 99%